Full-field shingle uplift measurements using StereoDIC: Comparison of single and double sealant three-tab shingle responses when subjected to hurricane velocity winds. Issue 224 (May 2022) - Rajan, Sreehari; Myers, Troy; Sutton, Michael A.; Boozer, Max; Kidane, Addis; Ghorbani, Rahim; Matta, Fabio
Abstract: For the first time, the vision-based measurement method Stereo Digital Image Correlation (StereoDIC) is applied successfully to quantitatively assess the response of asphalt shingles installed in a model roofing system and subjected to hurricane velocity winds. By mounting a low profile asphalt-shingled plywood roof facsimile without building firmly to a rigid steel frame and supplying sustained winds of 67.1 m/s perpendicular to the leading edge region, StereoDIC measurements were obtained at 1 Hz to measure the full-field uplift displacements for shingles sealed using either single or double sealant strips. By varying the sealant activation process (time and temperature), the effect of installation in winter and summer seasons is also quantified throughout the wind loading process. Results indicate that with lower temperature sealant activation, both single and double sealant shingles sustained catastrophic failure within a short time when the wind speed reached 67.1 m/s, with the double sealant system lasting for about 500 s; visual inspection of the separation surfaces for the low temperature activation showed large specular reflecting regions, indicating either no bonding or minimal adherence. For a higher sealant activation temperature, (a) both single and double sealant shingles remained intact for more than 2 h in 67.1 m/s wind speeds, with no sealant separation observed and (b) displacements for the shingle with double sealant strips were significantly lower than for the single sealant system, confirming the efficacy of a double sealant strip system. As a general observation, StereoDIC measurements clearly show that shingle uplift displacement is not constant across the width of a shingle tab, with the edges of the shingle (tab cutout regions) having significantly larger uplift displacements that may serve as sealant separation initiation sites. Highlights: Stereo digital image correlation employed for in situ measurement of uplift displacement of asphalt shingles. Asphalt shingles sealed using single and double sealant strips and at two different activation temperatures are evaluated. Lower activation temperature can result in partial bonding of sealant; one of the major causes of premature failure. Corners of the shingle undergo significantly larger uplift displacements.